Surgical Treatment of Clubfoot in Children with Moebius Syndrome - Maurizio De Pellegrin; Lorenzo Marcucci; Lorenzo Brogioni; Giovanni Prati (MDPI AG, 2021)
Moebius syndrome (MS) is a rare disease, with paralysis of the VI and VII cranial nerves, frequently associated with clubfoot (CF). The aim of this study was to evaluate surgical treatment of CF in MS, providing its peculiarities. Between 1990 and 2019, we collected data of 11 MS patients with unilateral (n = 5) or bilateral (n = 6) CF, for a total of 17 feet (9R,8L). Six patients (3M,3F) for a total of 10 feet (6R,4L) were treated elsewhere, performing first surgery at an average age of nine months, and in our hospital for relapse surgery at an average age of 4.5 years (Group 1). Five patients (3M, 2F), for a total of seven feet (3R,4L), were primarily treated in our hospital with a peritalar release according to McKay at an average age of 9.4 months (Group 2). Diméglio score was used to assess CF severity. Three questionnaires were submitted for evaluation of subjective and functional results: American Orthopedics Foot and Ankle Society for Hindfoot (AOFAS), Foot and Ankle Outcome Score (FAOS), and Foot and Ankle Ability Measure (FAAM). Average AOFAS/FAOS/FAMM scores were 82.8, 84.8, and 82.3 for Group 1, and 93.2, 94.7, and 95.1 for Group 2 at an average follow-up of 16.9 and 13.3 years, respectively. The average Diméglio score improved from 15.5 to 4.8 in the long-term follow-up in Group 1 and from 14.6 to 3.8 in Group 2. The comparison between the groups showed better results for AOFAS, FAOS, and FAAM scores for Group 2, particularly for pain, function, and foot alignment and for the post-surgical Diméglio score. CF in MS is more severe and presented a higher relapse rate (58.8%) than idiopathic CF. Peritalar release showed no relapse and better subjective and functional results in the long-term follow-up compared to other surgical techniques